Clinical features of patients with designer‐drug‐related disorder in Japan: A comparison with patients with methamphetamine‐ and hypnotic/anxiolytic‐related disorders. Issue 5 (9th January 2014) - Matsumoto, Toshihiko; Tachimori, Hisateru; Tanibuchi, Yuko; Takano, Ayumi; Wada, Kiyoshi
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to clarify the clinical features of designer‐drug‐abusing patients through comparisons with methamphetamine‐abusing patients and hypnotics/anxiolytics‐abusing patients. Methods Information on 126 designer‐drug‐abusing patients, 138 methamphetamine‐abusing patients, and 87 hypnotics/anxiolytics‐abusing patients was extracted from the 2012 database of 'The Nationwide Mental Hospital Survey on Drug‐related Psychiatric Disorders' and the clinical variables of designer‐drug‐abusing patients compared with those of the other two groups. Results Multivariate analysis indicated the following significant differences between designer‐drug‐abusing patients and the other two types of patients: designer‐drug‐abusing patients were younger, included more men, had higher education and fewer relationships with antisocial groups, and included more patients meeting ICD‐10 F1 sub‐classification categories of 'Harmful use' and 'Psychotic disorders' than methamphetamine‐abusing patients. Compared with hypnotics/anxiolytics‐abusing patients, designer‐drug‐abusing patients were younger, included more men and more patients meeting criteria for 'Psychotic disorders', and more frequently cited 'peer pressure', 'unable to refuse', and 'seeking stimulation' as reasons for using the drug. Conclusion The advent of designer drugs has created a new class of drug abuse, and abuse of designer drugs may carry a strong psychosis‐inducing risk, exceeding that of methamphetamine.